How to Exercise Europe’s Power - Zielonka, J (Routledge, 2008)
In order to make it more effective as an actor on the international scene, the European Union is being urged to reverse its foreign policy priorities. EU enlargement policy has fallen out of grace and many want to see Europe acquire a “normal” foreign policy with a global rather than merely regional reach, significant military means and centralised governance. Management of various conflicts in Africa and Asia is also in vogue. Such a policy shift will define the nature of Europe's actorness. It is argued that, with all its defects, the EU performs quite well as a civilian regional power and efforts to transform it into a traditional military power with a global reach could make things worse rather than better.